Flora and vegetation of dry grasslands of Northeastern Ukraine, and problems of diversity conservation - Ronkin, Vladimir; Savchenko, Galina (Hacquetia, 2016)
The aim of this study was to describe the flora and vegetation of the grasslands of Northeastern Ukraine and to analyse how the steppe vegetation responds to grazing or its abandonment. We studied two gully systems in the east of the Kharkiv Region: the Regional Landscape Park “The Velykyi Burluk-Steppe” (steppe grasslands on chernozem soils; 10 sites) and the National Nature Park “Dvorichanskyi” (steppe grasslands on chalky outcrops; 5 sites). Longterm monitoring data exist for both these sites starting in 1991, shortly after grazing intensity reduced. We recorded the major grassland plant communities (reflecting their successional status) as well as their dominant species. Tree and scrub encroachment increased after management ceased. We conclude that (i) heterogeneous grazing (including ungrazed patches) in space and time is necessary in order to preserve grassland biodiversity in our study system; (ii) erosion of chalky outcrops (natural erosion as well as driven by cattle grazing) is a key factor promoting the richness of cretaceous species in steppe grassland.